Ceremonial Music of Ancestral Spirit Worship of the Ban Ta-Nod, Muang District, Nakhon Ratchasima Province - Panin, Kornsuang (Rangsit Music Journal, 2024)
The research is a qualitative research which aims at studying on ceremony, social reflection and culture along with researching on inheritance guidelines of Pi Ton Korat. It is found that Ban Ta-Nod villagers believes in ancestral spirit so in a year, the worship is held 2 times which are the Ceremony of Pronouncing Ancestor in the period of the waxing moon on the 3rd month and on the 6th month as the Ancestral Spirit Worship Ceremony. The Ceremony has 4 steps which are 1) Ancestral spirit invitation performs “Choenpee Natab Khaotomtidpoong.” 2) Raise a Spirit performs “Kaopee Natab Khaotomtidpoong” 3) Spiritual Dance performs “Kantrum Natab Ramsurng and Kamarelaikuay Natab Ramton” 4) Dispel the Unfortunate: Ton Korat performs without Pi Kaew Natab Khaotomtidpoong”. Pi Ton Korat contains musical instruments including Pi Kaew, Ton Korat, Ching, Chab Lek, and Krab. Such activities create reflections and social culture from cultivating a good conscience towards parents, benefactors, knowing the sins and penalties which leads to the villagers to rule themselves with moral principles and beliefs taught by their ancestors, creating love, unity, and caring for each other. For inheritance of Pi Ton Korat, both musicians and Ton Korat maker have fewer descendants due to many factors such as economic when the progress of culture has changed into the modern era, the values of the living of the local people affecting on the change of culture.